H1N1pdm09 infection in children: A case report of reemerging disease in COVID-19 pandemic - Puspaningtyas, Niken Wahyu; Nagrani, Dimple Gobind; Karyanti, Mulya Rahma; Fauzie, Rifan; Imanadhia, Ashfahani; Sarita, Raisa Cecilia; Putra, Reynaldo Rahima (Indonesian Pediatric Society, 2024)
An outbreak of H1N1 infection was first declared by the World Health Organization in 2009 and confirmed in the post-pandemic phase in 2010. Amid the COVID-19 pandemic, we found a confirmed case of H1N1pdm09 in Bunda Women and Children Hospital Jakarta. A 13-year-old boy was referred to our hospital after four days of hospitalization due to worsening tachypnea following a productive cough and fever. The patient had severe dyspnea with inspiratory effort and oxygen desaturation to 80%, therefore admitted to our pediatric intensive care unit. On physical examination, the patient had increased work of breathing, looked irritable, had a respiratory rate of about 40x/minute with non-rebreathing mask support, and crackles were heard in both lungs. Chest x-ray showed right bronchopneumonia. There was a history of a generalized seizure for less than 1 minute, which stopped spontaneously in previous hospital care. The patient was diagnosed with mucopolysaccharidosis at age six years old and has never received enzyme replacement therapy. Laboratory results revealed thrombocytopenia, leukopenia, neutrophilia, monocytosis, high c-reactive protein and procalcitonin, and elevated liver enzymes. The investigation of etiology was performed using the respiratory panel test and showed a positive real-time polymerase chain reaction for H1N1pdm09 and Influenza A. The patient was given oxygen therapy with a high-flow nasal cannula with an oxygen fraction of 40% and a flow of 20 liters per minute, fluid maintenance while fasting, antibiotics, inhaled beta-2 agonists, and a neuraminidase inhibitor (oseltamivir). The patient's clinical and laboratory markers improved on the third day of treatment, and he was discharged two days later.